Farmers' participation, social capital and benefits in water management in Sindh province of Pakistan - Sheikh, Muhammad Javed (2015)
Participatory irrigation management is one of the important tools to poverty reduction among farming communities that helps to provide individual and collective benefits, and enhance quality of life. Theoretical perceptive and developmental studies also established the significant relationship between participation, social capital and their benefits. But, hardly any researcher has considered social capital as mediator between participation and benefits, which the researcher perceived as a huge gap in those studies. Based on previous literature, the researcher developed a hypothetical model and focused on the farming communities to examine the relationship among different levels of participation, social capital and benefits. Simultaneously, the researcher identified the potential factors that may affect participation and social capital. The study also quantified the mediation effect of social capital between participation and benefits (individual and collective). In this regard, the cross-sectional data were collected on a valid and structured scale through personal interview method, using multi-stage cluster sampling from 457 farmers in Sindh province of Pakistan. The greater part of the questionnaire was adopted from previous literature and related theories. With regard to latent variables, the components of participation included were planning,implementation, and monitoring & evaluation; social capital contained bonding (trust), structural (group solidarity) and linking social capital (networking);economic benefits, psychological benefits and human capital assembled individual benefits; and, social benefits and environmental benefits were associated with collective benefits. Finally, descriptive analysis was performed by means of SPSS-20 and AMOS-20 was used to develop a structural equation modelling (SEM) to determine the relationship among selected variables. The results of the study divulged that the farmers of Sindh province reported medium level of participation in water management activities with regard to watercourse associations. Medium level of participation, consequently produced the same level of social capital, individual and collective benefits, which revealed the positive relationship among them. Multiple linear regression estimates divulged significant (p ≤ .05) relationships between participation and its predictors related to demographic (age and education), socio-economic (house type and residential locality), and farm characteristics (farm facilities, using underground water and watercourse position). Though, social capital was significantly influenced by canal water accessibility, drainage system availability,age of the farmers, total land holding, farming experience, and family size in the study area. However, only age factor has contributed significantly and positively on both, participation and social capital. Goodness-of-fit indices of structural equation modelling robustly supports the theoretical framework and revealed significant contribution of participation to benefits (individual and collective) and social capital; likewise, social capital with individual and collective benefits was also noteworthy. Moreover, mediatory role of social capital between participation and collective benefits was found significant as compared to individual benefits. Finally, it is concluded that social capital played an important role in gaining collective benefits (social and environmental benefits) to the farming communities in participatory irrigation management, Sindh province of Pakistan. Facts and findings of the study could be useful for governmental and nongovernmental organizations, while developing policies and projects of community development.